2019
DOI: 10.5194/isprs-archives-xlii-2-w13-407-2019
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Biomass and Yield at Harvest of Salt-Stressed Tomato Plants Using Uav Imagery

Abstract: Biomass and yield are important variables used for assessing agricultural production. However, these variables are difficult to estimate for individual plants at the farm scale and may be affected by abiotic stressors such as salinity. In this study, the wild tomato species, Solanum pimpinellifolium, was evaluated through field and UAV-based assessment of 600 control and 600 salt-treated plants. The aim of this research was to determine, if UAV-based imagery, collected one, two, four, six, seven and eight week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Other researchers have also carried out many studies in the field of multisensor data fusion and obtained the same results in studies on the monitoring of crop biomass, such as rice (Cen et al, 2019) and soybean (Maimaitijiang et al, 2020). In addition, different crops have different characteristics, and the same crop will show different characteristics under different growth conditions (Johansen et al, 2019;ten Harkel et al, 2020), which requires the use of different sensors to collect crop information comprehensively and screen out some information most related to biomass. The combination of data from multiple sensors is an effective method to improve the accuracy of biomass estimation.…”
Section: Multisensor Fusionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other researchers have also carried out many studies in the field of multisensor data fusion and obtained the same results in studies on the monitoring of crop biomass, such as rice (Cen et al, 2019) and soybean (Maimaitijiang et al, 2020). In addition, different crops have different characteristics, and the same crop will show different characteristics under different growth conditions (Johansen et al, 2019;ten Harkel et al, 2020), which requires the use of different sensors to collect crop information comprehensively and screen out some information most related to biomass. The combination of data from multiple sensors is an effective method to improve the accuracy of biomass estimation.…”
Section: Multisensor Fusionmentioning
confidence: 88%
“…On the one hand, it is difficult to obtain reliable CH data from LiDAR in some cases. Johansen et al (2019) found that dust storms can cause tomato plants to flatten and that once the tomato fruits become large and heavy, the weight may cause the branches to bend downward, thereby reducing the height of the plants. ten Harkel et al (2020) found that potatoes have complex canopy structures and grow on ridges, so it is difficult to visually determine the highest point of a specific position.…”
Section: Crop Heightmentioning
confidence: 99%
“…In addition, machine learning (ML) approach with UAV imagery has been used to estimate biomass of crops including wheat [24], rice [25,26], maize [22], and barley [27]. Except for studies by Moeckel et al [28] and Johansen et al [11,12], we did not identify any studies that used UAVbased time series to predict tomato plant biomass and yield at harvest at the plant level.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, they used the mapped traits to identify tomato plant accessions that performed the best in terms of yield. Johansen et al [12] researched the predictability of fresh shoot mass (SM), number of fruits (FN), and yield mass at harvest using UAV-based imagery and indicated that plant area, border length, width, and length of plant had the highest importance in the random forest approach to modeling of biomass and yield. Candiago et al [13] examined the vegetation vigor of vineyards and tomatoes using three different vegetation indices (VIs) based on orthoimages and demonstrated the great potential of high-resolution UAV data.…”
Section: Introductionmentioning
confidence: 99%